2016
DOI: 10.1177/0969733015604685
|View full text |Cite
|
Sign up to set email alerts
|

Defining dignity in end-of-life care in the emergency department

Abstract: Quality care in the emergency department includes paying attention to the dignity of people in the process of death. The dignity in the care of a dying person in the emergency department is defined by acknowledging the inherent value in each person, socio-environmental conditions and social and individual acceptance of death. Addressing these questions has significant repercussions for health professionals, especially nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 46 publications
0
29
0
1
Order By: Relevance
“…We trust that the emerging themes will be able to contribute to comprehending the phenomenon of the dignity in end‐of‐life care in the Emergency Department. Previous studies have shown that dignity in end‐of‐life care should be understood as a person's inherent value, where socio‐environmental conditions and conscious actions/attitudes are also involved as attributes of dignity (Fernández‐Sola et al., ). Other studies have identified the main problems that, according to professionals, affect dignity in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We trust that the emerging themes will be able to contribute to comprehending the phenomenon of the dignity in end‐of‐life care in the Emergency Department. Previous studies have shown that dignity in end‐of‐life care should be understood as a person's inherent value, where socio‐environmental conditions and conscious actions/attitudes are also involved as attributes of dignity (Fernández‐Sola et al., ). Other studies have identified the main problems that, according to professionals, affect dignity in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Not recognizing the imminence of death, the lack of knowledge or the inadequacy of palliative care all continue to contribute to the dying patient's arrival in the ED. However, the ED is a space designated for looking after those who are acutely ill, where death is associated more with the failure of science than an unavoidable stage of life (Fernández‐Sola et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Focused on attending to acute, life-threatening pathologies, caring for a dying patient in the ED can lead to problems related to stress, communication, fear and loneliness, and carries the risk of losing privacy, confidentiality and dignity [12]. For physicians and nurses, the dignity of a dying person in the ED is a value inherent to the person, as is respecting his/her autonomy, allowing accompaniment and respecting human rights [14]. The loss of this dignity may result from the dying person being exposed to a "cold" world, improvised care, a lack of physical space in which to die, family members' obstinacy and/or a lack of a palliative care culture in the ED [15].…”
Section: Introductionmentioning
confidence: 99%